Rancang Bangun Sistem Informasi Konversi Mata Kuliah Menggunakan Framework Laravel - Iskandar, Dedy; Erliyani, Ita; Eliyana, Fanni (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2024)
The rapid development of technology causes the need for information systems to increase to encourage people to carry out activities so that they can be carried out quickly and accurately, and are required to be able to make decisions using appropriate methods. so as to get benefits for the progress of information systems. The information system needed in handling the conversion process for course value must be precise and fast, errors in the process of inputting course grades and calculating value conversions and the process of recording the results of conversion of course grades. Currently, conversion handling is still done semi-computerized using Microsoft Excel. then a system is needed that can equalize or convert courses. The method used in this information system is the SDLC (System Development Life Cycle) method of the waterfall type model, which is expected to be able to easily determine the achievement of a system, where a website system that has been designed uses PHP with the Laravel Framework as its programming language and SQL as a container. database storage, and UML (Unified Modeling Language) as a system model to describe the flow of procedures in the form of objects consisting of Use Case Diagrams, Activity Diagrams, and Sequence Diagrams, The results of this test are in the form of data or information regarding the conversion of course scores. From the test results, it can be concluded that this system can perform the expected functions. Hopefully with this system, it can help the department section to check the conversion so that it can be seen whether the conversion of the course value is correct or not, so as to minimize re-conversion in value conversion processing.